Estimation of alighting counts for public transportation vehicle occupancy levels using reverse direction boarding - Kamer Özgün; Melih Günay; Doruk Başaran; Joseph Ledet (Journal of Public Transportation, 2023)
In order to improve the performance of a public transport system, it is important to know alighting counts as well as boarding counts at bus stops. While boarding is almost always available through a fare collection system, public transport systems usually do not count alighting passengers. This is either due to the overhead that may be required for passengers at exit or the installation of relatively expensive Automatic Passenger Counters (APC) counters at each vehicle. Therefore, such expensive deployments are mostly not encountered in public-transport systems. In our research, for round trip lines that are balanced in daily passenger counts on both forward and backward routes, the alighting counts of a target route are inferred using only the daily boarding data. Vehicle occupancy levels are determined on a trip basis owing to the characteristic boarding pattern of each line. The validity of the proposed method was determined and verified using video recordings of arbitrarily selected trips. Consequently, it may be possible to modify scheduling algorithms to improve vehicle fleet utilization and increase passenger comfort in public transportation.